PURWOSARI TOURISM VILLAGE DEVELOPMENT EFFORTS BASED ON LOCAL TOURISM INTEGRATED - Sari, Lusiana Puspita; Tsaro, Riza Laela; Handayani, Elfa Dikah Tri (Universitas Negeri Semarang, 2020)
Purwosari village has a lot of potential to be used as the main tourist village of Semarang City. However, there is no denying that there is still an inequality of tourism development patterns between other tourism potential areas which is quite striking because the quality between the regions is not evenly distributed. This article tries to explore the concept in the development of local tourism integrated natural tourism destinations, reviewed with a qualitative approach with strategy analysis methods and SWOT selection process. The results of the analysis refer to quantitative planning efforts to compile the prioritized list based on the ranking of the relative attractiveness of a viable and appropriate alternative action, namely the decision stage of QSPM (Quantitative Strategy Planning Matrix). Applications in the development of tourist village destinations, including: Construction of tourist facilities and facilities from the local government development fund; Recommendations for training the surrounding community to work on the potential natural appeal of the typical culture that exists to be packaged into a beautiful, unique and authentic tourist attraction; as well as the creation of a website as a market development by expanding the reach of online channels to achieve integrated strategy of development of Purwosari tourism village in creating a good private investment climate. Kelurahan Purwosari memiliki banyak potensi untuk dijadikan sebagai desa wisata unggulan Kota Semarang. Namun tidak dapat dipungkiri bahwa masih terjadi ketimpangan pola pengembangan wisata antar kawasan potensi wisata lainnya yang cukup mencolok karena kualitas antar kawasan belum merata. Artikel ini mencoba untuk menggali konsep dalam pengembangan destinasi wisata alam local tourism integrated, dikaji dengan pendekatan kualitatif dengan metode analisis strategi dan proses pilihan SWOT. Hasil analisis merujuk pada upaya perencanaan kuantitatif untuk menyusun the prioritized list berdasarkan ranking daya tarik relatif dari alternatif tindakan yang layak dan tepat guna, yaitu tahap keputusan QSPM (Quantitative Strategy Planning Matrix). Aplikasi dalam pengembangan destinasi desa wisata, meliputi: Pembangunan sarana dan fasilitas wisata dari dana pengembangan pemerintah daerah; Rekomendasi pelatihan masyarakat sekitar untuk menggarap potensi daya tarik alam budaya khas yang ada untuk dikemas menjadi daya tarik wisata yang indah, unik dan otentik; serta Pembuatan website sebagai pengembangan pasar dengan memperluas jangkauan saluran online hingga mencapai integrated strategy pengembangan desa wisata Purwosari dalam menciptakan iklim investasi swasta yang baik.